2018
DOI: 10.18488/journal.61.2017.61.28.42
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Common Errors in ESL Descriptive Writing among Chinese Private School Students in Malaysia

Abstract: Article History

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 13 publications
1
17
1
Order By: Relevance
“…In addition, the results of this study was also not in line with Husin & Nurbayani's study (2017) who explained that the average score of thesis written in English by university students were relatively good quality. The finding of this study also showed slight difference to a study done by Nair & Hui (2018) who found that female students made significantly less errors than male students in their descriptive writing. Since all respondents of this study were female students, there was no presented comparison.…”
Section: The Factors Inhibiting and Improving The Students' Writing Scontrasting
confidence: 92%
See 1 more Smart Citation
“…In addition, the results of this study was also not in line with Husin & Nurbayani's study (2017) who explained that the average score of thesis written in English by university students were relatively good quality. The finding of this study also showed slight difference to a study done by Nair & Hui (2018) who found that female students made significantly less errors than male students in their descriptive writing. Since all respondents of this study were female students, there was no presented comparison.…”
Section: The Factors Inhibiting and Improving The Students' Writing Scontrasting
confidence: 92%
“…Studies on writing skills have been conducted in other countries. A study by Nair & Hui (2018) found that senior students in Kuala Lumpur, especially female students, made significantly less errors than male students in their descriptive writing. Trinh & Truc (2014) mentioned that genre-based approach significantly improved Vietnamese undergraduate students' ability in writing argumentative essays.…”
Section: The Process and Problems Of Efl Learners In English Writing:mentioning
confidence: 99%
“…According to Furner (2017), to address the issue of anxiety among their students, the inclusion of literature and writing have proven effective (Furner, 2017;Mokhtar, 2017;Mustafa, Tourkia, and Ramadan, 2017;Nair and Hui, 2018;Gumusgul, 2018;Kögce and Aslandag, 2018;Kyrychenko, 2018). It is also suggested that teachers use children's literature to combat anxiety by using these materials in a shared setting to foster connections in a more meaningful ways along with the inclusion of "writing, discussion, and the use of manipulatives as they relate to the story in the children's literature book".…”
Section: Introductionmentioning
confidence: 99%
“…This is a completely false belief Brannon. 1995;Firdaus, 2010. Applications designed with RFID would be possible to be as an wireless integrated devices such as cellular phones, tablets, sensor so that the application can ubiquitously be accessed Lahiri, 2005;Nair & Hui, 2018. The RFID technology is a wireless communication method that by mounting the IC chip RFID tags on objects, read the unique value recorded in the RFID tag, and to distinguish objects with RFID tags with the value called operates (Önder, 2018;Zheng,2018;Anwar, 2018).…”
Section: Radio Frequency Identification (Rfid)mentioning
confidence: 99%